Circulating tumour cells and cell-free DNA in pancreatic ductal adenocarcinoma - Gall,TM; Belete,S; Khanderia,E; Frampton,AE; Jiao,LR (American Journal of Pathology, 2019)
Pancreatic cancer is detected late in the disease process and has an extremely poor prognosis. A blood-based biomarker that can enable early detection of disease, monitor response to treatment, and potentially allow for personalised treatment, would be of great benefit. This review analyses the literature regarding two potential biomarkers: circulating tumour cells (CTCs) and cell-free DNA (cfDNA) with regards to pancreatic ductal adenocarcinoma (PDAC). The origin of CTCs and the methods of detection are discussed and a decade of research examining CTCs in pancreatic cancer is summarized, including both levels of CTCs and analyzing their molecular characteristics, and how this may affect survival in both advanced and early disease and allow for treatment monitoring. The origin of cfDNA is discussed and the literature over the past 15 years is summarized. This includes analyzing cfDNA for genetic mutations and methylation abnormalities which has the potential to be used for PDAC detection and prognosis. However, the research certainly remains in the experimental stage warranting future large trials in these areas.